ODET: An Arduino-based Overheat Detector for Household Appliances - Carvajal, Kim Lourenz S. (Animo Repository, 2022)
There were 443 cases of fire caused by electrical appliances from 2015-2017. It is considered the second most common cause of fire in the Philippines not due to open flames (PSA, 2018). To solve this problem, the researchers developed an overheat detector that powers down an appliance using an Arduino Uno Board and a relay. It used an LM35 sensor to detect the temperature and a buzzer to create an alarm. It needs to be able to detect changes in temperature with a ± 5% measurement error. As well as notify users if an appliance starts overheating with a 95% accuracy of detection. A Hot Bath Test consisting of 12 trials per temperature level ranging from 80°C-150°C in intervals of 10°C was done to test the accuracy of the temperature sensor. The computed average error of the mean which indicates the average error the temperature reading will have was 1.7% while the average standard deviation which indicates how much the reading will tend to deviate from the mean measured values was 0.4333. The computed F-1 Score, which measures how accurate the prototype can detect an overheat situation, was 0.67. Functionality tests were done in which the prototype successfully shut down the electric fan when the control temperature reaches the threshold level and keeps the electric fan working when it does not. The development of this device will help prevent and lessen fires, leading to the prevention of millions worth of both properties and life.